2017
DOI: 10.29252/jhs.5.4.1
|View full text |Cite
|
Sign up to set email alerts
|

Associated Factors of Anxiety among Acute Coronary Syndrome Patients in Kelantan and Terengganu

Abstract: Background and purpose: Anxiety is a common condition among acute coronary syndrome (ACS) patients. This syndrome often goes unrecognised and can persist for months to years, while impacting substantially the quality of life. Therefore, this study aimed to identify the associated factor of anxiety among ACS patients in Hospital Universiti Sains Malaysia (USM) and Hospital Sultanah Nur Zahirah (HSNZ). Materials and Methods:This cross-sectional study involved ACS patients admitted to Hospital USM, Kelantan and H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 33 publications
0
1
0
Order By: Relevance
“…Anxiety becomes a psychological response when there is an attack and it is reportedly that more than 86.3% of ACS patients experience anxiety during their treatment in the hospital (Abu Ruz et al, 2010;Wan-Nor-Asyikeen et al, 2017). Anxiety is caused by chest pain, bad conditions, helplessness and death threat (Meneghetti et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Anxiety becomes a psychological response when there is an attack and it is reportedly that more than 86.3% of ACS patients experience anxiety during their treatment in the hospital (Abu Ruz et al, 2010;Wan-Nor-Asyikeen et al, 2017). Anxiety is caused by chest pain, bad conditions, helplessness and death threat (Meneghetti et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The current study involved a cross-sectional study conducted in two selected hospitals in Kelantan and Terengganu, Malaysia (9). All ACS patients admitted to the medical wards, including general wards, cardiac rehabilitation ward (CRW), and coronary care unit (CCU) in both hospitals participated in the study (9).…”
Section: Methodsmentioning
confidence: 99%
“…The current study was conducted to identify the associated factors of stress among ACS patients. This article is derived from a study by Wan-Nor-Asyikeen et al, a part of which was previously published (9). However, both studies identified different outcomes, whereas the previous study was published on anxiety-related factors among ACS patients.…”
Section: Introductionmentioning
confidence: 99%